2023
DOI: 10.1021/acs.inorgchem.3c00649
|View full text |Cite
|
Sign up to set email alerts
|

A d-Methionine-Bonded Nanosized Heteropolyoxotungstate with Photocoloration

Abstract: A d-methionine-bonded nanosized arsenotungstate, Ba9K10H6­[{As2W19O67­(H2O)}2­{AsW9O33}2­{W3O6­(H2O)­(d-Met)}2­{W2O4(OH)(d-Met)}]·60H2O [1; d-Met = d-methionine (C5H11NO2S)], is constructed without the use of lanthanide ions. The polyanion of 1 contains two {As2W19O67(H2O)}14– building blocks and two {B-β-AsW9O33}9– subunits, integrated together with a {W2O4(OH)(d-Met)}2+ and two {W3O6(H2O)(d-Met)}5+ subclusters. Interestingly, 1 displays a highly reversible photocoloration property with a half-life (t 1/2) ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Also, fatty carboxylic acid-, aromatic carboxylic acid-, and amino acid-decorated POMo and POV derivatives have all been reported in abundance. However, the development of carboxylic-based polyoxotungstates (POTs) was slower than that of POMos and POVs. It is rare that the incorporation of organic carboxylic acid to the polyanion framework covalently generated POT hybrid clusters. , We inferred that the activity was inferior between tungstate–oxygen segments and carboxylic acid, which further results in the O atom in the POM {WO 6 } octahedron being substituted with the O atom of carboxylic acid with difficulty …”
Section: Introductionmentioning
confidence: 98%
“…Also, fatty carboxylic acid-, aromatic carboxylic acid-, and amino acid-decorated POMo and POV derivatives have all been reported in abundance. However, the development of carboxylic-based polyoxotungstates (POTs) was slower than that of POMos and POVs. It is rare that the incorporation of organic carboxylic acid to the polyanion framework covalently generated POT hybrid clusters. , We inferred that the activity was inferior between tungstate–oxygen segments and carboxylic acid, which further results in the O atom in the POM {WO 6 } octahedron being substituted with the O atom of carboxylic acid with difficulty …”
Section: Introductionmentioning
confidence: 98%
“…7,8 Moreover, POMs-based hybrid materials have made significant progress in the field of color change. For example, Niu's research team reported a nanosized arsenotungstate, Ba 9 Color-changing materials are a new type of functional materials with development potential, which can change color with external stimuli. 10 According to the external stimulus sources, they are mainly divided into thermochromic, photochromic, electrochromic, piezoelectric materials, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, the loss of different amounts of {MoO 6 } blocks in SiMo 12 O 40 forms a multitude of lacunary polyoxoanions, and the tamolybdate with nine isomers can provide infinite possibilities for synthesis. , Moreover, POMs-based hybrid materials have made significant progress in the field of color change. For example, Niu’s research team reported a nanosized arsenotungstate, Ba 9 K 10 H 6 [{As 2 W 19 O 67 (H 2 O)} 2 {AsW 9 O 33 } 2 {W 3 O 6 (H 2 O)­( D -Met)} 2 {W 2 O 4 (OH)­( D -Met)}]·60H 2 O ( D -Met = D -methionine), with highly reversible photochromic properties in 2023 …”
Section: Introductionmentioning
confidence: 99%